Clinical features of hypophosphatemic osteomalacia induced by long-term low-dose adefovir dipivoxil - Zhu S; Yang YH; Gao RW; Li R; Zou YZ; Feng L; Zhang B (Dove Medical Press, 2017)
Sheng Zhu, Yu-Hui Yang, Rong-Wei Gao, Ran Li, Yu-Zhen Zou, Lei Feng, Bo Zhang Department of Pharmacy, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China Objective: To investigate the predictors of hypophosphatemic osteomalacia induced by adefovir dipivoxil (ADV) and to monitor for early detection. Patients and methods: Hospitalized patients who were diagnosed with ADV-related hypophosphatemic osteomalacia were recruited and retrospectively analyzed in our hospital from January 2012 to December 2016. A telephone interview was conducted at 1, 3, 6, 9, 12, and 24 months after cessation of ADV.Results: In the 8 patients enrolled in the study, the hypophosphatemic osteomalacia symptoms developed at an average of 5.14 (4–7) years since ADV treatment (10 mg/d). The average alkaline phosphatase (ALP) level was 279.50 (137–548) U/L, which was significantly higher than the normal level (45–125 U/L). The serum phosphorus level was an average of 0.59 (0.43–0.69) mmol/L, which was lower than the normal range (2.06–2.60 mmol/L). Serum calcium levels of the enrolled patients remained within normal limits. Reduced estimated glomerular filtration rate (eGFR <29 mL/min/1.73 m2) was seen in 4 cases. The clinical manifestations were mainly progressive systemic bone and joint pain, frequent fractures, trouble in walking, height reduction (4–6 cm), and so on. After cessation of ADV, symptoms like bone pain resolved gradually. Serum phosphorus level restored to normal in 4.5 months after the withdrawal of ADV. However, in 4 patients, renal function failed to return to normal in 24 months.Conclusion: More attention should be paid to the duration of ADV treatment. The level of serum phosphorus and ALP, as well as renal function, should be monitored for early detection of potential adverse drug reactions. Keywords: adefovir dipivoxil, hypophosphatemic osteomalacia, long term, follow-up, serum phosphate, renal tubular dysfunction